Regulation of Ethical Aspects of Electronic Medical Records in Indonesia’s Positive Law and Implementation in Hospitals - Prajany, Joshua Jonah; Silitonga, Lamria; Sapsudin, Asep (Research Horizon, 2025)
The transformation of medical records into electronic form through Minister of Health Regulation Number 24 of 2022 aims to enhance healthcare service systems based on the principles of data security and confidentiality. However, the implementation of Electronic Medical Records (EMR) requires more than technical readiness; it must also adhere to core medical ethics principles, including autonomy, privacy or confidentiality, integrity, authentication, availability, access control, and non-repudiation. This study aims to analyze how these ethical principles are regulated and implemented in Indonesian hospitals. Using a normative legal research method with a statutory approach, this study examines relevant laws and regulations along with literature from scientific publications between 2020 and 2025. The findings reveal that although the regulation of EMR ethics is relatively comprehensive, its practical application remains limited. Key issues include the absence of specific SOPs, insufficient technological capacity, and limited attention to patient autonomy. While many hospitals share basic RME features such as login access, integration, and data backup, only some adopt advanced security measures like auto log-off or electronic signatures. This study concludes with recommendations to harmonize regulations with field practices, improve data protection, and ensure equitable technological infrastructure for sustainable EMR implementation in Indonesia.